ANALISIS KEBERLANJUTAN FISKAL INDONESIA TAHUN 2000-2012 - Ria Marisa (Bina Ekonomi, 2015)
Indonesia’s budget deficit that is financed by debt could increase the government debt. This causes the governemnt budget increase continuously in order to payback the debt. Fiscal sustainability is achieved when the government is capable to manage its debt so that the debt will not burden the future government budget. VECM is employed in this study to determine whether Indonesia’s fiscal is sustainable or not. After calculating the actual condition of the ratio of primary balance to GDP, it is concluded that Indonesia’s fiscal is sustainable for the year of 2000 and 2012.